2013
DOI: 10.1055/s-0033-1349474
|View full text |Cite
|
Sign up to set email alerts
|

Achtsamkeitsbasierte kognitive Therapie (MBCT) für Patienten mit Zwangsstörung – Eine Adaptation des Originalkonzepts

Abstract: Mindfulness-based cognitive Therapy (MBCT) has shown to be effective in the relapse prevention and treatment of several psychiatric disorders. However, MBCT has not yet been applied in OCD (Obsessive-compulsive Disorder). This article proposes an adaptation of the eight-session group program for patients with residual symptoms after cognitive behavioural treatment (CBT) with exposure. It has proven feasible and was considered helpful by patients within the framework of a pilot study 1. Apart from an overview o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A new study reported the beneficial effects of MBCT in OCD, depression and anxiety symptoms as well as obsessive beliefs through improving mindfulness skills and self-compassion in the experimental group vs. controls (18). In addition, other third wave treatment approaches such as Acceptance and Commitment Therapy (ACT) and Mindfulness Based Stress Reduction are also reported as beneficial in relapsed OCD symptoms (14,(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…A new study reported the beneficial effects of MBCT in OCD, depression and anxiety symptoms as well as obsessive beliefs through improving mindfulness skills and self-compassion in the experimental group vs. controls (18). In addition, other third wave treatment approaches such as Acceptance and Commitment Therapy (ACT) and Mindfulness Based Stress Reduction are also reported as beneficial in relapsed OCD symptoms (14,(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%